Perspektif Siswa dan Guru Terhadap Pengorganisasian Pojok Baca dalam Pembelajaran Literasi di SDN Karangduak II - Zahroh, Fatimatus; Ar-Romdhani, Umar Farouq; Safitri, Fina (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to explore the perspectives of students and teachers regarding the organization of reading corners in literacy learning at SDN Karangduak II. This research employs a qualitative approach with a case study design. The research subjects consisted of six students who were actively involved in utilizing the reading corner and one classroom teacher directly engaged in its management. Data were collected through in-depth interviews, observations, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The findings indicate that the book collection in the reading corner does not fully align with students’ interests and academic needs, resulting in low student utilization. Teachers acknowledge the importance of the reading corner but face limitations in training related to its management and integration into learning activities. Updating the book collection, implementing more structured management, and actively involving students in organizing the reading corner are essential to improving its effectiveness. The study concludes that the organization of the reading corner at SDN Karangduak II needs improvement to better support students’ literacy learning.